Evaluation of Useful Biomechanical Parameters On Scoliosis Using Finite Element Method - Khademi, Midiya; Nikoo, Ali (International Clinical Neuroscience Journal, 2020)
Background: Scoliosis is a deformity of the vertebral column, and shape-changing and deformation of the spine are some critical factors that can cause this abnormality. This condition causes some problems like deflection of the spine in the coronal plane toward medial or lateral. Cobb angle is a measurement for the investigation of the severity of this condition. There are several effective therapies suggested for the reduction of the Cobb angle for patients who has this abnormality. It has suggested that before applying external forces to correct this condition, biomechanical evaluation of this deformity, can be useful during diagnosis. Methods: The purpose of this study is the evaluation of Cobb angle correction using external forces. For this aim first, the dimensional data of the patient’s vertebrae are extracted from CT-scan images using Mimics software, and the vertebral column modeled in Catia software for finite element analysis (FEA). Afterward, the model was imported into Abaqus software to evaluate the effect of forces on the spine model. The study was done by assuming two cases for the spine, one-piece (without a nucleus) and two-piece (with a nucleus) intervertebral disc. Results: After studying the results of this simulation, it concluded that after applying gravity force to these two cases, the percentage of Cobb angle’s reduction was about 0.05 for a two-piece disc and about -0.18 for the one-piece disc. Therefore, the two-piece disc assumption was better for analyzing this parameter. The results of maximum displacement and von misses stress show that the two-piece disc is accurate. Conclusion: In order to investigate which analysis is appropriate to be selected, choosing a twopiece intervertebral disc model is superlative. Whether our goal is only to examine the stress which is present in the patient model, choosing a one-piece disc is a more optimal duo to take much less time.